2002
DOI: 10.1093/emboj/21.8.2019
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae MGS1 is essential in strains deficient in the RAD6-dependent DNA damage tolerance pathway

Abstract: Saccharomyces cerevisiae Mgs1 protein, which possesses DNA-dependent ATPase and single strand DNA annealing activities, plays a role in maintaining genomic stability. We found that mgs1 is synthetic lethal with rad6 and exhibits a synergistic growth defect with rad18 and rad5, which are members of the RAD6 epistasis group important for tolerance of DNA damage during DNA replication. The mgs1 mutant is not sensitive to DNA-damaging agents, but the mgs1 rad5 double mutant has increased sensitivity to hydroxyurea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 53 publications
(83 reference statements)
5
103
0
3
Order By: Relevance
“…The authors suggested an alternative model in which PCNA monoubiquitination may disrupt its interactions with a protein(s) that inhibits binding to the TLS polymerases. To date no such candidate protein has been identified, although we notice a recent report [130] that Mgs1, a protein with homology to E. coli RuvB and eukaryotic clamp loader protein RFC, as well as DNA-dependent ATPase activity and DNA-annealing activities [131,132], associates with PCNA and appears to repress the RAD6 pathway in the absence of exogenous damage. Other concerns with the above paradigm include the stability of monoubiquitinated PCNA, particularly in mammalian cells, that extends past the expected time required to bypass the damage [122], which would allow persistent TLS with unnecessarily increased mutation rates.…”
Section: Regulated Access Of Y-family Polymerases To the Damage Sitementioning
confidence: 93%
“…The authors suggested an alternative model in which PCNA monoubiquitination may disrupt its interactions with a protein(s) that inhibits binding to the TLS polymerases. To date no such candidate protein has been identified, although we notice a recent report [130] that Mgs1, a protein with homology to E. coli RuvB and eukaryotic clamp loader protein RFC, as well as DNA-dependent ATPase activity and DNA-annealing activities [131,132], associates with PCNA and appears to repress the RAD6 pathway in the absence of exogenous damage. Other concerns with the above paradigm include the stability of monoubiquitinated PCNA, particularly in mammalian cells, that extends past the expected time required to bypass the damage [122], which would allow persistent TLS with unnecessarily increased mutation rates.…”
Section: Regulated Access Of Y-family Polymerases To the Damage Sitementioning
confidence: 93%
“…Lysine 123 of Rad6 Is Essential for Lys-4 Methylation of Histone H3-Rad6 is a ubiquitin-conjugating enzyme (E2) (17) involved in DNA repair (17,18), DNA damage-induced mutagenesis (19,20), meiosis (21), transposition of retrotransposons (22), and gene silencing (23). Rad6 catalyzes ubiquitination of Lys-123 of histone H2B (24).…”
Section: Development Of a Biochemical Screen In 96-well Plates To Idementioning
confidence: 99%
“…Rad6 in diverse cellular processes (17)(18)(19)(20)(21)(22). However, our genome-wide survey of S. cerevisiae revealed that none of the mutants missing these (non-essential) Rad6-interacting proteins, including those that act with Rad6 in DNA damage repair (Rad18 and Rex4) and the N-end rule-dependent protein degradation pathway (Ubr1 and Ubr2), are involved in methylation of histone H3 Lys-4 (Fig.…”
Section: Involvement Of Other Rad6-interacting Proteins In Lys-4 Methmentioning
confidence: 99%
“…MGS1 encodes for a DNA-dependent ATPase with ssDNA annealing activities that has been suggested to compete with the PRR pathway for resolution of fork stalling lesions [6,37,38]. RAD30 has been implicated in an error-free form of translesion synthesis [39,40] that some have placed in the PRR pathway [41].…”
Section: Epistasis Analysis Defines a Role For Exo1 In The Mms2 Errormentioning
confidence: 99%